Tinjauan Hukum terhadap Pelaku Tindak Pidana Promosi Situs Judi Online melalui Media Sosial - Kristo Korneles Joroh; Adensi Timomor; Sam Julius Richard Saroinsong (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This research aims to examine and analyze how law enforcement is carried out against perpetrators of criminal acts of promotion of online gambling sites through social media, as well as to identify the things that become the background of the perpetrators of promoting these gambling sites. The research conducted uses normative legal research methods, namely research focused on literature review of applicable positive legal norms. This research uses a statutory approach, as well as a conceptual approach that relies on a literature study of relevant legislation and legal doctrine. The results show that the activity of promoting online gambling sites through social media is included in illegal acts as regulated in Article 27 paragraph (2) jo. Article 45 paragraph (3) of Law No. 1 of 2024, but in practice law enforcement still faces serious challenges. Therefore, synergy between law enforcement, digital regulators, and social media platforms is needed to more effectively address the spread of promotional content for online gambling sites.